CEO Political Ideology and Voluntary Forward-Looking Disclosure - Elnahas, Ahmed; Gao, Lei; Hossain, Md Noman; Kim, Jeong-Bon (Journal of Financial and Quantitative Analysis, 2024)
Abstract This study investigates whether the management earnings forecasts of Republican and Democratic CEOs differ due to systematic differences in their information disclosure preferences. We find that Republican CEOs prefer a less asymmetric information environment than Democrat CEOs, and thus make more frequent, timelier, and more accurate disclosures than Democrat CEOs. Results using the propensity score matched sample and difference-in-differences analysis show that our results are unlikely to be driven by potential endogeneity. Our results are robust to controlling for various CEO characteristics and are stronger for firms with higher levels of institutional ownership and litigation risk.